Kompetensi Pedagogik Guru MI dalam Mengimplementasikan Kurikulum - Tulus Budi Santoso; Evarianisa Endang Trisnani (Jurnal Studi Pendidikan Dasar, 2024)
This study aims to examine the pedagogical competence of Madrasah Ibtidaiyah (MI) teachers in implementing the Merdeka Curriculum and to identify the challenges and strategies needed for its strengthening. The Merdeka Curriculum requires teachers to design student-centered learning, manage classrooms effectively, and conduct evaluations based on diagnostic and formative assessments. This study reveals various challenges faced by MI teachers, such as limited understanding of the new curriculum, lack of continuous training, limited digital literacy, and high administrative burdens. Furthermore, the study proposes strategies for strengthening pedagogical competence, including reflective practice-based training, development of teacher learning communities, mentoring and coaching support, and provision of adequate learning resources. The findings indicate that support from various stakeholders is crucial to enhance MI teachers’ pedagogical competence, ensuring optimal implementation of the Merdeka Curriculum and positive impacts on the quality of primary education in Indonesia.